The multiple roles of C-type lectin receptors in cancer - Li, Qiao (Frontiers in Oncology, 2023)
C-type lectin receptors are a family of immune response receptors that can bind with a broad repertoire of ligands. It can function as innative immune receptors to surveillance bacteria, fungi, and virus invasions. The expressions of C-type lectin receptors (CLRs) are found in different types of tumors. But the role of C-type lectin receptors in cancer is not fully elucidated. And the underlying mechanisms of CLRs in carcinogenesis and tumor development remained unknown. It is known that CLRs bind to the glycosylated antigen on the cancer cells, regulating cancer cell invasion, migration, and metastasis. Meanwhile, the recognition of tumor glycans by antigen-presenting cells can stimulate antitumor immune response and induce immune tolerance. Also, some types of CLRs can be used as diagnostic markers for tumor cells, suggesting that C-type lectin can function as a new tumor therapeutic target and potential biomarkers. Given the therapeutic potential of CLRs in tumor treatments and the emerging roles of CLR in the tumor hallmarks, the multiple roles of CLRs in cancer were summarized in this review.